Type checking and normalisation - Chapman, James Maitland (2009)
This thesis is about Martin-Löf's intuitionistic theory of types (type theory). Type theory is at the same time a formal system for mathematical proof and a dependently typed programming language. Dependent types are types which depend on data and therefore to type check dependently typed programming we need to perform computation(normalisation) in types.